A Review of Electrospun Conductive Polyaniline Based Nanofiber Composites and Blends: Processing Features, Applications, and Future Directions. (30th December 2015) - Abd Razak, Saiful Izwan; Wahab, Izzati Fatimah; Fadil, Fatirah; Dahli, Farah Nuruljannah; Md Khudzari, Ahmad Zahran; Adeli, Hassan
Abstract : Electrospun polymer nanofibers with high surface area to volume ratio and tunable characteristic are formed through the application of strong electrostatic field. Electrospinning has been identified as a straight forward and viable technique to produce nanofibers from polymer solution as their initial precursor. These nanofiber materials have attracted attention of researchers due to their enhanced and exceptional nanostructural characteristics. Electrospun polyaniline (PANI) based nanofiber is one of the important new materials for the rapidly growing technology development such as nanofiber based sensor devices, conductive tissue engineering scaffold materials, supercapacitors, and flexible solar cells applications. PANI however is relatively hard to process compared to that of other conventional polymers and plastics. The processing of PANI is daunting, mainly due to its rigid backbone which is related to its high level of conjugation. The challenges faced in the electrospinning processing of neat PANI have alternatively led to the development of the electrospun PANI based composites and blends. A review on the research activities of the electrospinning processing of the PANI based nanofibers, the potential prospect in various fields, and their future direction are presented.